2020
DOI: 10.4085/1062-6050-190-19
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Among Middle-Aged Adults With Chronic Ankle Instability, Copers, and Uninjured Controls

Abstract: Context People with chronic ankle instability (CAI) display a lower regional and global health-related quality of life (HRQoL). Examinations of HRQoL outcomes associated with CAI have addressed younger adults, restricting our understanding of the long-term consequences of CAI. Objective To compare ankle regional and global HRQoL in middle-aged participants with and those without CAI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
1
20
2
1
Order By: Relevance
“…Foot and Ankle Disability Index (FADI) Activities of Daily Living and Sport subscales and Patient-Reported Outcomes Measurement Information System Adult Profile were used to assess regional and global health-related quality of life. It was observed that chronic ankle instability subjects had reduced regional and global quality of life than their age-matched healthy counterparts and copers [32].…”
Section: Discussionmentioning
confidence: 99%
“…Foot and Ankle Disability Index (FADI) Activities of Daily Living and Sport subscales and Patient-Reported Outcomes Measurement Information System Adult Profile were used to assess regional and global health-related quality of life. It was observed that chronic ankle instability subjects had reduced regional and global quality of life than their age-matched healthy counterparts and copers [32].…”
Section: Discussionmentioning
confidence: 99%
“…Among the ve subscales of the FAOS, the ADLs and FAQL had the highest proportions of ceiling values, indicating that a substantial proportion of participants might not have experienced any restriction in their daily activities, and they may also have a satisfactory social life. Previous studies showed that young adults with CLAI maintained su cient performance of their daily activities and an adequate quality of life [23], whereas older CLAI patients had poorer daily activities and quality of life compared to healthy older people [24]. Our study sample may have contributed to the high ceiling values in the FAOS's ADL and FAQL in that young patients have faster physical and mental recovery from neuromuscular dysfunction, as well as a faster return to routine ADLs and sports, compared to older patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Among the five subscales of the FAOS, the ADLs and FAQL had the highest proportions of ceiling values, indicating that a substantial proportion of participants might not have experienced any restriction in their daily activities, and they may also have a satisfactory social life. Previous studies showed that young adults with CLAI maintained sufficient performance of their daily activities and an adequate quality of life [ 28 ], whereas older CLAI patients had poorer daily activities and quality of life compared to healthy older people [ 29 ]. Our study sample may have contributed to the high ceiling values in the FAOS’s ADL and FAQL in that young patients have faster physical and mental recovery from neuromuscular dysfunction, as well as a faster return to routine ADLs and sports, compared to older patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%